2009
DOI: 10.1158/1078-0432.ccr-08-3131
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Ratio Is Predictive of Head and Neck Squamous Cell Carcinoma

Abstract: Purpose: The involvement of microRNAs in cancer and their potential as biomarkers of diagnosis and prognosis are becoming increasingly appreciated. We sought to identify microRNAs altered in head and neck squamous cell carcinoma (HNSCC) and to determine whether microRNA expression is predictive of disease. Experimental Design: RNA isolated from fresh-frozen primary tumors, fresh-frozen nondiseased head and neck epithelial tissues, and HNSCC cell lines was profiled for the expression of 662 microRNAs by microar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
198
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(216 citation statements)
references
References 41 publications
13
198
2
3
Order By: Relevance
“…It was recently published that the ratio of miR-221 to miR-375 was predictive for the outcome of head and neck squamous cell carcinoma (25). In our analysis, we found a consistent downregulation of miR-221 and an upregulation of miR-375, whereas the situation was reversed in the head and neck squamous cell carcinoma study.…”
Section: Discussionsupporting
confidence: 61%
“…It was recently published that the ratio of miR-221 to miR-375 was predictive for the outcome of head and neck squamous cell carcinoma (25). In our analysis, we found a consistent downregulation of miR-221 and an upregulation of miR-375, whereas the situation was reversed in the head and neck squamous cell carcinoma study.…”
Section: Discussionsupporting
confidence: 61%
“…Although several studies did not notice an upregulation of miR-375 in prostate carcinoma samples, various studies observed increased levels of this miRNA in prostate cancer serum samples (44,45). Publications confirm that miR-375 is downregulated in other cancer types such as cervical, lung, or head and neck carcinoma, as well as glioma (46)(47)(48)(49)(50) but upregulated in breast carcinoma (51). Likewise, miR-15a was previously shown to be downregulated in metastasizing prostate carcinoma (18).…”
Section: Discussionmentioning
confidence: 80%
“…Until very recently, miR-375 has been found to be deregulated in some malignancies, including live tumor with β-catenin mutation, head and neck squamous cell carcinoma and pancreatic adenocarcinomas [26][27][28][29], whereas little is known about the molecular targets of miR-375 in these cancer. To our knowledge, JAK2 may be the first identified target gene that is involved in the regulation of carcinogenesis by miR-375.…”
Section: Discussionmentioning
confidence: 99%